Tafsir Ayat Pendidikan Dalam Perspektif Klasik dan Kontemporer ; Analisis Surat Al-'Alaq Ayat 1-5 - Firnanda, Rizky; Syibly, Muhammad Roem; Nah, Juna (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study examines the interpretation of Surah Al-‘Alaq verses 1-5 in the context of education, comparing the perspectives of the classical mufassir Al-Qurtubi and the contemporary mufassir Muhammad Abduh. The background of this research lies in the importance of gaining a deeper understanding of Allah’s command to read and learn within the framework of Islamic education. The main focus of this study is to analyze how these two mufassirs interpret the verses, highlighting their differences and similarities regarding the role of education in the lives of Muslims. The research employs a qualitative method with a descriptive-analytical approach to explore the meaning of these verses in both intellectual and spiritual dimensions. The main findings reveal that Al-Qurtubi emphasizes the spiritual dimension of reading, viewing it as a means to strengthen faith and comprehend the greatness of Allah, while Muhammad Abduh stresses the importance of reading as a tool for acquiring knowledge that fosters the advancement of civilization. These two approaches complement each other, demonstrating that Islamic education should balance both spiritual and intellectual development. Therefore, this study concludes that an ideal Islamic education system must integrate religious values and general knowledge to contribute to the progress of the Muslim community in the future.